Ethnic group inequalities in coverage with reproductive, maternal and child health interventions: cross-sectional analyses of national surveys in 16 Latin American and Caribbean countries - Marilia Arndt Mesenburg, PhD; Maria Clara Restrepo-Mendez, PhD; Hugo Amigo, PhD; Alejandra D Balandrán, MPH; Maria Angelica Barbosa-Verdun, MSc; Beatriz Caicedo-Velásquez, PhD; Liliana Carvajal-Aguirre, MSc; Carlos E A Coimbra, Jr, PhD; Leonardo Z Ferreira, MSc; Maria del Pilar Flores-Quispe, MSc; Carlos Flores-Ramírez, MSc; Giovanna Gatica-Dominguez, PhD; et al. (Elsevier, 2018)
Summary: Background: Latin American and Caribbean populations include three main ethnic groups: indigenous people, people of African descent, and people of European descent. We investigated ethnic inequalities among these groups in population coverage with reproductive, maternal, newborn, and child health interventions. Methods: We analysed 16 standardised, nationally representative surveys carried out from 2004 to 2015 in Latin America and the Caribbean that provided information on ethnicity or a proxy indicator (household language or skin colour) and on coverage of reproductive, maternal, newborn, and child health interventions. We selected four outcomes: coverage with modern contraception, antenatal care coverage (defined as four or more antenatal visits), and skilled attendants at birth for women aged 15-49 years; and coverage with three doses of diphtheria-pertussis-tetanus (DPT3) vaccine among children aged 12-23 months. We classified women and children as indigenous, of African descent, or other ancestry (reference group) on the basis of their self-reported ethnicity or language. Mediating variables included wealth quintiles (based on household asset indices), woman's education, and urban-rural residence. We calculated crude and adjusted coverage ratios using Poisson regression. Findings: Ethnic gaps in coverage varied substantially from country to country. In most countries, coverage with modern contraception (median coverage ratio 0·82, IQR 0·66-0·92), antenatal care (0·86, 0·75-0·94), and skilled birth attendants (0·75, 0·68-0·92) was lower among indigenous women than in the reference group. Only three countries (Nicaragua, Panama, and Paraguay) showed significant gaps in DPT3 coverage between the indigenous and the reference groups. The differences were attenuated but persisted after adjustment for wealth, education, and residence. Women and children of African descent showed similar coverage to the reference group in most countries. Interpretation: The lower coverage levels for indigenous women are pervasive, and cannot be explained solely by differences in wealth, education, or residence. Interventions delivered at community level-such as vaccines-show less inequality than those requiring access to services, such as birth attendance. Regular monitoring of ethnic inequalities is essential to evaluate existing initiatives aimed at the inclusion of minorities and to plan effective multisectoral policies and programmes. Funding: The Bill & Melinda Gates Foundation (through the Countdown to 2030 initiative) and the Wellcome Trust.